ISLAMIC RELIGIOUS EDUCATION STRATEGY IN MULTICULTURAL SMP NEGERI 2 PANCUR BATU - Windri Irawati; Hasan Asari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Indonesia's multicultural diversity presents a distinctive challenge in implementing Islamic Religious Education (PAI) within heterogeneous public schools. This study aims to explore the PAI learning strategies applied at SMP Negeri 2 Pancur Batu, a public school with a balanced composition of Muslim and non-Muslim students (50:50) from various ethnic and religious backgrounds. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and documentation involving PAI teachers, the vice principal, subject teachers, and students. The findings reveal that PAI teachers implement three primary strategies: diversity-based classroom management through a parallel learning system, contextual teaching and learning that connects PAI content to students' real-life experiences, and the integrated cultivation of multicultural values ​​across every lesson. These strategies proved effective in fostering a harmonious, tolerant, and conflict-free school environment, while simultaneously strengthening the moderate and inclusive character of Muslim students.